Expression of urinary exosomal miR-136-5p in diabetic kidney disease and evaluation of its clinical diagnostic value - Shanshan Zheng; Jiao Li; Chaoqun Ma; Baobao Wang; Sen Lin; Zunsong Wang; Wenbin Li; Ping Wang; Ping Chen; Hao Li; Jing Wu; Yipeng Liu (Scientific Reports)
Abstract Diabetic kidney disease (DKD) has become a major cause of chronic kidney disease and end-stage renal disease. Numerous studies have indicated that exosomal miRNAs play a crucial role in the pathophysiological processes of DKD. We screened differentially expressed miRNAs in urinary exosomes from patients with DKD using the GEO database and performed PCR validation both in patients who were pathologically diagnosed and clinically diagnosed. We assessed the clinical diagnostic value of urinary exosomal miRNAs using ROC curves, analyzed the correlation between miRNAs and clinical indicators, predicted the target genes using the miRTarBase database and explored the potential signaling pathways involved through functional enrichment analysis. Screening results showed that the expression of miR-136-5p was significantly elevated in the DKD group compared to the DM group, with significance maintained in validation samples. The sensitivity and specificity of miR-136-5p for diagnosing DKD were 72.2% and 78.4%, respectively, with an area under the curve of 0.722. Additionally, the expression of miR-136-5p was positively correlated with UACR, urea nitrogen, cystatin C, chronic kidney disease progression risk stratification indicators, and negatively correlated with eGFR. 152 target genes of miR-136-5p were predicted and enriched in 25 pathways, including insulin secretion, cAMP signaling pathway, and sphingolipid signaling pathway.